Use of allogeneic stem cell transplantation for moderate–severe Glanzmann thrombasthenia. (3rd October 2015) - Walz, Amy; Lenzen, Alicia; Curtis, Brian; Canner, Jason; Schneiderman, Jennifer
Abstract: Glanzmann thrombasthenia (GT) is a rare, autosomal recessive coagulopathy characterized by either qualitative or quantitative abnormalities of the membrane glycoprotein αIIbβ3 complex leading to bleeding tendencies, ranging from purpura to life-threatening hemorrhage. Although patients can be managed with supportive measures including platelet transfusions, complications such as alloimmunization are possible. Allogeneic stem cell transplantation (ASCT) can be indicated in severe cases of GT. We report the case of an eight-month-old girl diagnosed with moderate–severe GT, who was successfully treated with a reduced-intensity, human leukocyte antigen (HLA)-identical ASCT.